Coronavirus Disease 2019 State Guidelines on Elective Surgery: Considerations for Plastic and Reconstructive Surgeons. Issue 5 (May 2020) - Sarac, Benjamin A.; Schoenbrunner, Anna R.; Wilson, Stelios C.; Chiu, Ernest S.; Janis, Jeffrey E.
Abstract : Background: Vague recommendations regarding elective surgery have been proposed by national organizations in an attempt to conserve personal protective equipment and to protect healthcare workers during the coronavirus disease 2019 pandemic. In response, some states have attempted to provide more clear guidance. Methods: An internet search was performed to identify and analyze what guidance each state published through government websites through April 10, 2020. Results: Thirty-five states and the District of Columbia published guidance in the form of either a recommendation or a mandate. Procedures relating to cosmetics and malignancy were found to be mentioned in 4 and 12 states, respectively, but ultimately lacked case-specific information. Conclusions: Current government and state recommendations do not provide clear guidance on how plastic and reconstructive surgeons should approach elective surgeries. Ultimately, it is the responsibility of all plastic and reconstructive surgeons to operate under appropriate law while individualizing their practices to best suit the needs of their patients while being mindful of resource limitations and exposure risks.